A decision game for informal learning - Souza, Bruno Mendes (2022)
Lifelong learning implies that people are willing to change their attitude, way of thinking or acting, usually based on some objective. For that, a decision game was developed for iOS and Android devices, using the Unity Game Engine. The premise of the game puts the player in the role of a business manager facing situations that require a decision. The game presents a card based mechanics, allowing the player to choose between two options, sliding the card to the right or to the left, influencing the outcome of the game. The game allows to use different decks of cards. The experience was assessed with the assistance of three instruments: closed questions questionnaire, written exams before and after playing the game and observation.